Effects of a Health Literacy Promotion Program on Health Behaviors in Early Adolescents with Over-Nutrition in Tha Uthen District, Nakhon Phanom Province - Chuthanitchaya, Kanyachat; Mangkarakeree, Nutcharat; Meekusol, Saovaros (Journal of The Royal Thai Army Nurses, 2025)
This study was quasi-experimental research conducted with aim of examining effects of the health literacy promotion program on obesity prevention behavior in early adolescents with over-nutrition in Tha Uthen District, Nakhon Phanom Province, The sample was selected by systematic random sampling and divided into an experimental group of 31 people who received a program to promote health literacy on obesity prevention behaviors for a period of 8 weeks, and comparison group of 31 people who lived normal lives. Pre-and post-test data were collected by using questionnaires. The data obtained were analyzed by using descriptive statistics. Comparison of the variances in mean pre-and post-test scores between the experimental and comparison groups used t–test statistics. The findings revealed that the mean post-test obesity prevention behavior score in the experimental group was statistically and significantly higher than that of the comparison group (p-value < 0.001). The mean post-test dietary intake behavior score was statistically and significantly higher than that of the comparison group (p-value < 0.001). The mean exercise behavior score was statistically and significantly higher than that of the comparison group (p-value < 0.001). The mean emotional behavior score was statistically and significantly higher than that of the comparison group (p-value < 0.001). Therefore, the health literacy promotion program on obesity prevention behavior in early adolescents with over-nutrition should be applied to adolescents who are overnourished with continuous monitoring of weight control.